RECOGNITION AND ENFORCEMENT OF FOREIGN ARBITRAL AWARDS (World Bulletin of Management and Law, 2024)
This article delved into the important aspects of the recognition and enforcement process of foreign arbitral awards across different jurisdictions. The role of the New York Convention as the legal framework that establishes a foundation for the recognition and enforcement of foreign arbitral awards and its main provisions were thoroughly studied and analyzed. The grounds for refusal of recognition and enforcement of arbitral awards were discussed in detail. It also studied the challenges that may arise in the recognition and enforcement procedures of foreign arbitral awards. In addition to the challenges, the practices and strategies of several countries concerning the recognition and enforcement policy of foreign arbitral awards were investigated.